Occupational Health and Safety Management System for the Motorway Company IMBAVIAL E.P. Province of Imbabura - Cabrera Vallejo, Mario (2017)
The present research work was carried out in the company INBAVIAL E.P., whose economic activity is of civil engineering the risk is high according to what the categorization establishes. The purpose of this research topic is to implement a system of Occupational Health and Safety Management based on Ecuadorian legislation, this management system allows to have an administrative, technical, human and operational talent, which means that they are four pillars Which are executed by the management system, for it is part of a manual, which has procedures and instructions, formats for records that are auditable and verifiable, that allow to comply with the Deming cycle.In carrying out this research, it is verified that the occupational health and safety management system improves the working conditions of the company, due to the total control of each of the activities and working conditions. The change of this company is radical because the management supports with the economic, technological and human resources looking for the prevention of occupational risks (PRL), promoting the safety and health of the workers through the identification, evaluation and control of the dangers and Risks associated with a work environment, in addition to encouraging the development of activities and measures necessary to prevent risks.